Bridge to Practice: A Qualitative Evaluation of Joint Medical Program (JMP) International Medical Graduates Perceived Preparedness for Professional Practice - Michelle Foot; Khanrin Vashum; Pavana Ballal; Lisa Lampe (Journal of Medical Education and Curricular Development, 2024)
OBJECTIVES This study sought to examine the views of international graduates regarding how they perceived the Joint Medical Program Bachelor of Medicine (JMP BMed) undergraduate training prepared them to practice in a health system different from that in which they had studied. Eighteen international graduates of the JMP between 2010 and 2017 inclusive agreed to be interviewed face-to-face. METHODS JMP BMed international graduates were interviewed using 18 standardized questions to elicit perceptions of their preparedness to practice and reflections on their training experience. The interview data were qualitatively analyzed, and the main themes were identified and categorized. RESULTS Overall, the international graduates of the JMP BMed curriculum felt well-prepared for tasks associated with communication, self-directed learning, and approaching mental health issues. Conversely, they perceived the level of clinical exposure and experience as inadequate in preparing them for the expected level of medical knowledge and responsibility. They also felt underprepared for navigating a different health system. CONCLUSIONS The strengths and weaknesses identified in the JMP BMed program in its preparation of international graduates, particularly those who chose to practice in their country of origin, are of relevance for all medical schools that enrol international students. Greater awareness of the needs of international medical students returning home to practice may be of value for future curriculum planning purposes to ensure that medical schools optimally prepare their graduates to practice with confidence in a range of healthcare systems.